Effect of natural and synthetic pigments on growth performance, relative weight of some organs and cecal characteristics of young broilers - Sánchez DiPalma, R.; Amaya Gonzalez, F.; Rodríguez Bertot, R.; Aroche Ginarte, R.; Martínez, Y. (Cuban Journal of Agricultural Science, 2025)
To evaluate whether dietary supplementation with pigments (natural and synthetic) had a growth-promoting effect in broilers at the early stage (0-10 days), 480 one-day-old Ross 308® male chickens were randomly assigned to four treatments (four replicates and 30 birds). The experimental treatment consisted of a control diet and the supplementation with 1 % of Bixa orellana, 1 % of Murraya koenigii and 0.03 % of canthaxanthin. The experimental diets did not affect (P>0.05) the viability, however, Bixa orellana diet increased (P<0.05) the body weight compared to the other experimental groups, although this treatment did not change (P>0.05) the feed intake and feed conversion ratio in relation to the control diet. The treatments did not modify the relative weight of the gizzard, pancreas, and heart (P>0.05). However, the Bixa orellana and Murraya koenigii groups decreased (P<0.05) the relative weight of the proventriculus and cecum and the liver and abdominal fat, respectively. Furthermore, the canthaxanthin group increased (P<0.05) the relative weight of lymphoid organs and small intestine (P<0.05). Moreover, Bixa orellana diet decreased (P<0.05) the pH, total coliforms, Enterobacteriaceae and Escherichia coli in the cecum compared to the other diets, and the Murraya koenigii group increased (P<0.05) the population of lactic acid bacteria. Also, in this organ (cecum), yeast quantification decreased (P<0.05) due to canthaxanthin and the fungal population did not change among treatments (P>0.05). Dietary supplementation with Bixa orellana has a natural growth-promoting effect, as well as a marked antimicrobial effect against common cecal Enterobacteriaceae of broilers.